Answer:
41° and 49°
Step-by-step explanation:
Given:
Angle 1 and angle 2 are complementary angles.
The measures of angle 1 is 8 more than the measure of angle 2.
Question asked:
Determine the measures of angle 1 and 2.
Solution:
Let ∠1 = ![x](https://tex.z-dn.net/?f=x)
Then ∠2 =
(given)
As we know that sum of complementary angles are 90° and here given that angle 1 and angle 2 are complementary angles which means,
∠1 + ∠2 = 90°
°
°
Subtracting both sides by 8,
°![-8](https://tex.z-dn.net/?f=-8)
°
Dividing both sides by 2,
°
∠1 =
°
∠2 = ![x+8](https://tex.z-dn.net/?f=x%2B8)
∠2 =
= 49°
Therefore, the measures of angle 1 and 2 are 41° and 49°
Proof -
So, in the first part we'll verify by taking n = 1.
![\implies \: 1 = {1}^{2} = \frac{1(1 + 1)(2 + 1)}{6}](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%201%20%20%3D%20%20%7B1%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B1%281%20%2B%201%29%282%20%2B%201%29%7D%7B6%7D%20)
![\implies{ \frac{1(2)(3)}{6} }](https://tex.z-dn.net/?f=%20%5Cimplies%7B%20%5Cfrac%7B1%282%29%283%29%7D%7B6%7D%20%7D)
![\implies{ 1}](https://tex.z-dn.net/?f=%5Cimplies%7B%201%7D)
Therefore, it is true for the first part.
In the second part we will assume that,
![\: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} = \frac{k(k + 1)(2k + 1)}{6} }](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%20%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7Bk%28k%20%2B%201%29%282k%20%2B%201%29%7D%7B6%7D%20%20%7D)
and we will prove that,
![\sf{ \: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 1 + 1) \{2(k + 1) + 1\}}{6}}}](https://tex.z-dn.net/?f=%5Csf%7B%20%5C%3A%20%7B%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%201%20%2B%201%29%20%5C%7B2%28k%20%2B%201%29%20%2B%201%5C%7D%7D%7B6%7D%7D%7D)
![\: {{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 2) (2k + 3)}{6}}](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%202%29%20%282k%20%2B%203%29%7D%7B6%7D%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k (k + 1) (2k + 1) }{6} + \frac{(k + 1) ^{2} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%20%28k%20%2B%201%29%20%282k%20%2B%201%29%20%7D%7B6%7D%20%2B%20%20%5Cfrac%7B%28k%20%2B%201%29%20%5E%7B2%7D%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k(k+1)(2k+1)+6(k+1)^ 2 }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%28k%2B1%29%282k%2B1%29%2B6%28k%2B1%29%5E%202%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)\{k(2k+1)+6(k+1)\} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%5C%7Bk%282k%2B1%29%2B6%28k%2B1%29%5C%7D%20%7D%7B6%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2 +k+6k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%20%2Bk%2B6k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2+7k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%2B7k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(k+2)(2k+3) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%28k%2B2%29%282k%2B3%29%20%7D%7B6%7D%20)
<u>Henceforth, by </u><u>using </u><u>the </u><u>principle </u><u>of </u><u> mathematical induction 1²+2² +3²+....+n² = n(n+1)(2n+1)/ 6 for all positive integers n</u>.
_______________________________
<em>Please scroll left - right to view the full solution.</em>
Answer:
the numbers are 18 and 38
Step-by-step explanation:
x =smaller integer and y =larger integer
Answer:
x=-5
Step-by-step explanation:
Answer:
Step-by-step explanation:
![log(3x + 1) - log(2x + 5) = 1 \\ \\ log \: \frac{3x + 1}{2x + 5} = log \: 10..( \because \: log \: 10 = 1) \\ \\ \frac{3x + 1}{2x + 5} = 10 \\ \\ 3x + 1 = 20x + 50 \\ 3x - 20x = 50 - 1 \\ \\ - 17x = 49 \\ \\ x = \frac{49}{ - 17} \\ \\ \huge \purple{ \boxed{x = - \frac{49}{17}}} \\](https://tex.z-dn.net/?f=log%283x%20%2B%201%29%20-%20log%282x%20%2B%205%29%20%3D%201%20%5C%5C%20%20%5C%5C%20log%20%20%5C%3A%20%5Cfrac%7B3x%20%2B%201%7D%7B2x%20%2B%205%7D%20%20%3D%20log%20%5C%3A%2010..%28%20%5Cbecause%20%5C%3A%20log%20%5C%3A%2010%20%3D%201%29%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B3x%20%2B%201%7D%7B2x%20%2B%205%7D%20%20%3D%2010%20%5C%5C%20%5C%5C%20%203x%20%2B%201%20%3D%2020x%20%2B%2050%20%5C%5C%203x%20-%2020x%20%3D%2050%20-%201%20%5C%5C%20%20%5C%5C%20%20-%2017x%20%3D%2049%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B49%7D%7B%20-%2017%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Chuge%20%5Cpurple%7B%20%5Cboxed%7Bx%20%3D%20%20-%20%20%5Cfrac%7B49%7D%7B17%7D%7D%7D%20%20%5C%5C%20)